Eletrocardiografia computadorizada em cães da raça Beagle - Gava, F.N. [UNESP]; Paulino-Junior, D. [UNESP]; Pereira-Neto, G.B. [UNESP]; Pascon, J.P.E. [UNESP]; Sousa, M.G. [UNESP]; Chanpion, T. [UNESP]; Camacho, Aparecido Antonio [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2011)
Estudaram-se os parâmetros eletrocardiográficos utilizando-se os métodos convencional, computadorizado e computadorizado impresso de 30 cães da raça Beagle clinicamente normais. As medidas eletrocardiográficas dos três diferentes traçados foram analisadas na derivação DII. A comparação entre os métodos revelou diferença nos valores da onda P, onda R, complexo QRS, intervalo QT e intervalo PR e na polaridade da onda T. Este fato deve ser levado em consideração, na dependência do método a ser utilizado.

Electrocardiographic parameters were studied in thirty healthy adult Beagles, using conventional and computerized methods and reading the computerized registration printed on paper. The electrocardiographic measurements of the three different tracings were analyzed in lead II. The results obtained showed that there are differences among the three methods for P wave, R wave, QRS complex, QT interval, PR interval and polarity of the T wave. Special attention should be given to these differences, depending on the chosen method.
Computerised electrocardiograph in Beagle dogs
Keywords: Dog; electrocardiogram; Cão; eletrocardiograma